Analisis Kebutuhan Mahasiswa terhadap Pengembangan E-LKPD Berbasis Keterampilan Proses Sains pada Mata Kuliah Konsep Dasar Biologi dan Lingkungan - Risdalina Risdalina; Desy Rosmalinda; Issaura Sherly Pamela; Andi Gusmaulia Eka Putri (Prosiding Seminar Nasional Ilmu Pendidikan, 2026)
This study aims to analyze the needs of students in the Elementary School Teacher Education Program at Jambi University regarding the development of electronic student worksheets based on science process skills (SPS) in the Basic Concepts of Biology and the Environment course. The low ability of students in science process skills, especially in formulating hypotheses, planning experiments, and using tools/materials, is attributed to the lack of teaching materials that systematically train SPS. The study adopted a quantitative descriptive approach, with participants selected through purposive sampling. Data were collected using a student needs questionnaire and analyzed with both quantitative and qualitative descriptive statistics. The results indicated that students prefer visual and kinesthetic learning styles. They showed a high preference for practice-based learning (average 4.57), interactive media (videos, simulations, animations) at 4.43, and visualization with images and graphics at 4.37. There is also a high demand for electronic student worksheets, with expectations for interactive features (4.20), step-by-step guidance for KPS (4.13), and digital accessibility (4.00). Students are highly positive about the product, as seen from their willingness to use electronic student worksheets (4.23) and their expectations for improved science process skills and contextual understanding of biology and the environment (4.47). Therefore, the development of SPS-based electronic student worksheets is highly needed by students.